1998
DOI: 10.1159/000055486
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Eye Drops Protective against Ultraviolet Radiation

Abstract: Background: To test the effectiveness of commercially available ultraviolet (UV)-protective eye drops (8-hydroxy-1-methylchinolinium methylsulphate) which are recommended for protection against both solar and artificial UV radiation. Methods: The spectral transmission in the wavelength range from 250 to 500 nm was investigated in 1-nm steps using a high-resolution double monochromator with holographic gratings of 2,400 lines/mm and a 1,000-watt halogen lamp as light source. The transmission spectrum was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…The UV absorption of the tear film itself is inadequate for this purpose [11,12]. Commercial UV blockers also failed to ensure physical UV absorption at normal thickness, although they were strongly anti-oxidative biochemically in our experiments [6].…”
Section: Discussionmentioning
confidence: 61%
“…The UV absorption of the tear film itself is inadequate for this purpose [11,12]. Commercial UV blockers also failed to ensure physical UV absorption at normal thickness, although they were strongly anti-oxidative biochemically in our experiments [6].…”
Section: Discussionmentioning
confidence: 61%
“…Both theoretically (Boote et al 2005) and experimentally (Goh et al 2008) fibril volume fraction has been shown to be directly proportional to the elastic modulus. Using the data in Daxer et al (1998) and Malik et al (1992) and the methodology described in Meek & Leonard (1993) the volume fraction per unit fibril length can be shown to increase from about 0.25 (age 40) to 0.29 (age 80), an increase of 16 per cent. This therefore suggests that up to 16 per cent of the observed stiffness increase over these four decades can be attributed to changes in microstructure.…”
Section: Discussionmentioning
confidence: 97%
“…Increased stiffness could result from age-related changes in corneal microstructure as well as changes in collagen fibril strength. For example, between the ages of 40 and 80, collagen fibril diameters increase (Daxer et al 1998) and collagen centre-to-centre interfibrillar spacings decrease (Malik et al 1992) and this leads to an increase in the fibril volume fraction. Both theoretically (Boote et al 2005) and experimentally (Goh et al 2008) fibril volume fraction has been shown to be directly proportional to the elastic modulus.…”
Section: Discussionmentioning
confidence: 99%
“…The interplay of these collagen constitutents results in a tissue in which the collagen fibrils have a tightly controlled range of diameters between 29 and 34 nm that are spaced at a center-to-center distance of 64-67 nm. 48 These characteristics of regular size and spacing of collagen fibrils are the essential elements that provide the cornea with optical transparency at visible wavelengths. 46,49,50 The interaction of collagen and the other extracellular matrix elements with water is important when considering energy transport processes within the tissue.…”
Section: A Tissue Composition and Morphologymentioning
confidence: 99%